Protracted Internal Displacement as a Moral Challenge to African Renaissance - Rwezaura, Deogratias M. (Asian Horizons, 2024)
The African renaissance (rebirth) and the rise of Africans towards a more united, just, peaceful and dignified life raise great aspirations. To achieve these aspirations, guns must be silenced, and broken communities and relationships mended so that the forcibly displaced can safely return to their homes. However, the persistent internal displacements across the continent due largely to the resurgence of armed conflict and coup d’états notwithstanding climate-induced displacements pose a moral challenge to the desired goals of a new Africa. The search for solutions to these challenges require an interdisciplinary approach that draws from socio-pastoral and ethical humanitarian wisdom.